Public Health Across Partisan Lines: What Has Changed Since the Onset of COVID-19. (January 2021) - Sellers, Katie; Leider, Jonathon P.; Gollust, Sarah; Gendelman, Moriah; Castrucci, Brian
Abstract : Two polls were conducted by an independent polling firm in September 2018 and July 2020 to assess public perceptions of public health departments and services among voters in the United States. The poll also sought to uncover changes in perception before and after the onset of COVID-19. A random sample was drawn from state voter files proportional to the national registered voter population by state, with quotas set by specific demographics to ensure representativeness. Overall, 1800 individuals participated between the 2 polls and weights were used in the analysis to adjust for nonresponse. From 2018 to 2020, respondents' familiarity with local public health departments rose 11% and their perception of the importance of the public health department to community health increased by 16%. In addition, support for public health departments and services differed significantly by political affiliation. In 2020, 85% of Democrats perceived the public health department to be very important while only 62% of their Republican counterparts felt similarly. Public health advocates have a unique opportunity to demand sustained funding for public health as American voters are more familiar and supportive of public health departments now than they were before the pandemic. In addition, policy makers, elected officials, and political candidates have the opportunity to leverage these data to fight for the health of their communities.